2014
DOI: 10.2807/1560-7917.es2014.19.34.20883
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and hospitalisation rates of Lyme borreliosis, France, 2004 to 2012

Abstract: Stockholm University and WHO, within a project funded by the European Commission (EVK2-2000-00070), reviewed the impacts of climate change and adaptation on Lyme borreliosis (LB) in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 101 publications
3
45
0
Order By: Relevance
“…Data can be collected through repeated cross-sectional retrospective surveys, as has been implemented in the Netherlands and some other countries by means of GP surveys [5,11-15]. Other options would be implementation through prospective or retrospective sentinels among hospitals and GP practices [16-18]. These options work mainly on a voluntary basis and are shown to provide high response rates and good regional and national estimates to identify temporal and spatial trends [12].…”
Section: Surveillance Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…Data can be collected through repeated cross-sectional retrospective surveys, as has been implemented in the Netherlands and some other countries by means of GP surveys [5,11-15]. Other options would be implementation through prospective or retrospective sentinels among hospitals and GP practices [16-18]. These options work mainly on a voluntary basis and are shown to provide high response rates and good regional and national estimates to identify temporal and spatial trends [12].…”
Section: Surveillance Scenariosmentioning
confidence: 99%
“…At lower administrative levels or in a sentinel setting, surveillance of neuroborreliosis may be relatively insensitive, since neuroborreliosis is a relatively rare outcome compared with EM, occurring in 3–38% of LB cases, whereas EM occurs in 60–95% of all diagnosed LB manifestations [11,16,17,24] (Table 2). …”
Section: Surveillance Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Tick-borne diseases (TBD) are a public health issue worldwide as trends in several studies indicate that their incidence has increased in Europe and America over the past two decades (Bacon et al, 2008;Lindgren and Jaenson, 2006;Randolph, 2004;Vandenesch et al, 2014). Therefore several questions arise, namely, why this emergence?…”
Section: Introductionmentioning
confidence: 97%
“…Currently, available official data on LB incidence in Germany range between 77.6/100,000 for the state of Brandenburg and 5.7/100,000 for the urban area of Berlin (Fülöp and Poggensee, 2008). In the absence of nationwide notification data it seems attractive to provisionally rely on other sources of data with comprehensive coverage such as hospital discharge data used in a recent study from France (Vandenesch et al, 2014) or claims data of health insurance companies. Following the latter approach, a study reported an average annual incidence of 261/100,000 for the diagnosis "LB" (Müller et al, 2012).…”
Section: Introductionmentioning
confidence: 98%